2010
DOI: 10.1152/ajplung.00408.2009
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of lung inflammation by the Epstein-Barr virus protein Zta

Abstract: Several studies have implicated gamma-herpesviruses, particularly Epstein-Barr virus (EBV), in the progression of idiopathic pulmonary fibrosis. The data presented here examine the possible role that EBV plays in the potentiation of this disease by evaluating the pulmonary response to expression of the EBV lytic transactivator protein Zta. Expression of Zta in the lungs of mice via adenovirus-mediated delivery (Adv-Zta) produced profibrogenic inflammation that appeared most pronounced by day 7 postexposure. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 87 publications
(105 reference statements)
1
18
0
Order By: Relevance
“…However, the pattern of inflammatory factors is altered following the switch from the latent EBV life cycle to the lytic life cycle. Previous studies have shown that BZLF1 regulates inflammation (10,48), and our present study provided new evidence indicating that BZLF1 attenuates TNF-␣ and IFN-␥ expression as well as expression of a series of other inflammatory factors. In addition, BZLF1 abolishes the response to TNF-␣ and IFN-␥ stimuli by inhibiting the expression of the major TNF receptor TNFR1 and the IFN-␥ receptor, respectively (21)(22)(23).…”
Section: Discussionsupporting
confidence: 75%
“…However, the pattern of inflammatory factors is altered following the switch from the latent EBV life cycle to the lytic life cycle. Previous studies have shown that BZLF1 regulates inflammation (10,48), and our present study provided new evidence indicating that BZLF1 attenuates TNF-␣ and IFN-␥ expression as well as expression of a series of other inflammatory factors. In addition, BZLF1 abolishes the response to TNF-␣ and IFN-␥ stimuli by inhibiting the expression of the major TNF receptor TNFR1 and the IFN-␥ receptor, respectively (21)(22)(23).…”
Section: Discussionsupporting
confidence: 75%
“…38,39 To detect kinetochore MTBP, H-40 antibody (Santa Cruz Biotechnology) was used. Z-sectioned images were obtained on a Zeiss Axioplan II deconvolution microscope (Carl Zeiss, Thornwood, NY, USA) and processed as described by Guenther et al 40 Flow cytometric analysis. For cell cycle analysis, cells fixed with 70% ethanol at À201C were stained with PI solution (Invitrogen) in the presence of 10 mg/ml RNase, followed by flow cytometric analysis using FACSCalibur (BD Biosciences).…”
Section: Discussionmentioning
confidence: 99%
“…After three washes with 3% BSA in PBS, the sections were incubated with streptavidinconjugated horseradish peroxidase (1:2,000 dilution) (016-030-084; Jackson ImmunoResearch Laboratories) in the same solution for 1 h at room temperature. Visualization with diaminobenzidine and counterstaining were as previously described (17).…”
Section: Animal Model K-rasmentioning
confidence: 99%
“…Bronchoalveolar lavage (BAL) was performed after intubation of mice with a 20-gauge 1.25-in. catheter secured in place with a suture (17). Mice were lavaged with 5 ϫ 0.8 ml of ice-cold lavage buffer (0.137 M sodium chloride, 2.7 mM potassium chloride, 12 mM phosphate buffer, 0.4 mM EDTA, pH 7.4).…”
Section: Animal Model K-rasmentioning
confidence: 99%
See 1 more Smart Citation